2022
DOI: 10.3390/land11050736
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Geosites and Geomorphosites in the Lut Desert of Shahdad Region for Potential Geotourism Development

Abstract: In the fields of geology, economics, history, cultural studies, and ecology, tourism can be the basis for proper planning, for sustainable tourism management, and for economic development. The Dasht-e Lut is one of the most significant desert areas in Iran due to its exemplary desert patterns and world-famous landscapes, such as the kaluts and nebkhas landforms. Furthermore, it is the hottest spot in the world and can attract adventurous tourists, amongst others, from around the globe. The purpose of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The present study employed the Pralong method, as did other studies [37,62,66,67], and its results indicated that using the Pralong method to study geotourism and regional tourism is appropriate and has produced results for a variety of tourism sites in the study area. Geomorphosites can also be prioritized using the Pralong method, such as similar works that were conducted in different regions of the world, where the relationship between geomorphosites and landscapes matters [87].…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…The present study employed the Pralong method, as did other studies [37,62,66,67], and its results indicated that using the Pralong method to study geotourism and regional tourism is appropriate and has produced results for a variety of tourism sites in the study area. Geomorphosites can also be prioritized using the Pralong method, such as similar works that were conducted in different regions of the world, where the relationship between geomorphosites and landscapes matters [87].…”
Section: Resultsmentioning
confidence: 54%
“…Of particular interest in this study is the pursuit of the benefits of transdisciplinarity through which local or indigenous ecotourism is conducted [16], the importance of ecotourism in the sustainable development of thematic products, and activities belonging to geoparks [34]. In other studies, geotourism is based on geology and landscapes [10,35], including features of natural, subnatural, and humanised landscapes [36,37]. Landscapes themselves become territorial resources for tourism [38,39], promoting the image of the countryside [40,41] and conservation [42][43][44][45], geotourism and recreation activities, and preservation [31,46,47].…”
Section: Research Backgroundmentioning
confidence: 99%
“…Other interesting geosite assessment efforts are the ones performed by Tomić and Božić [95], Štrba [106], Kubalíková and Kirchner [107], Suzuki and Takagi [108], and Raeisi et al [109]. All the above works have one point in common, i.e., to have performed the assessment of geosites and geomorphosites for geotourism development purposes.…”
Section: Geosite Assessmentmentioning
confidence: 99%
“…The demand for tourism products linked to geoheritage exploitation in NPAs and interest in the study of the geotouristic potential of geomorphosites are increasing [6,7,[12][13][14][15]. A wide range of assessment methodologies to determine the geotourist potential of geomorphosites and to improve their management and conservation have been developed over the past few years [6,[11][12][13][16][17][18][19][20][21].…”
Section: Introduction: Natural Protected Areas Geomorphosites and Tou...mentioning
confidence: 99%